Examining Borderline Personality Beliefs in terms of Shame, Guilt and Compassion - Kozak, Ekin Doğa (My University, 2019)
Shame and guilt as self-conscious emotions are defined to occur as a result of evaluation of one's own self. The intensity and frequency of these emotions can be related to develop and/or maintain personality disorders. On the other hand, self-compassion which is defined as evaluation of one's own self without judgement can be a protective factor against psychological problems. The aim of this study is to investigate the relationship between self-conscious emotions (shame and guilt) and borderline personality beliefs (BPB) and the role of self-compassion and fear of compassion on this relationship. Data collection was carried out via online questionnaires from 208 volunteer participants from Turkey with an age range between 18 and 56 (M = 26.84, SD = 6.96). Participants were given Demographic Information Form, Guilt and Shame Scale, Borderline Subscale of Personality Belief Scale, Self-Compassion Scale, Fear of Self-Compassion Subscale of Fears of Compassion Scale and Marlowe-Crowne Social Desirability Scale. According to the results, shame was positively while guilt was negatively correlated with borderline personality beliefs. Shame and guilt had a high positive correlation with each other but at the same time their direction of correlation with borderline personality beliefs was opposite. By creating four different categories with high and low ends of shame and guilt scores, their relationship with borderline personality beliefs were reexamined. The results indicated that shame- free guilt category had the lowest borderline personality belief scores. Hierarchical regression analyses were applied in order to discover the predictors of BPB. Shame and guilt explained 17% of the variance of BPB in the first step. In the second step, self-compassion and fear of compassion raised the explained variance to 46%. Mediational effects of self-compassion and fear of compassion were tested via Process Macro. It was found that borderline personality beliefs were mediated by self-compassion and fear of compassion. As results suggest, in treatment interventions of borderline personality beliefs, it is important to cultivate self-compassion and to decrease fear of compassion. The implications of this study would be beneficial for a better understanding of borderline personality.